Soil zinc availability from inorganic and chelated zinc sources and its accumulation in maize, evaluated by Kinetica: a computational modeling platform - Pinto, Webert Saturnino (2021)
Zinc deficiency is one of the most frequent among the micronutrients. In intensely weathered soils that are already poor in Zn, applications of large amounts of lime, often without adequate incorporation, and of phosphate fertilizers are common causes of Zn deficiencies, especially in crops that are more sensitive to low Zn availability. Especially in these cases, to determine the most efficient source of Zn to be applied, it is crucial to evaluate all the variables involved in the relationship between the source, the soil, and the plant. Although the supply of Zn in the form of mineral sources may in principle be more economically viable, these compounds may present low efficiency, especially in certain soil conditions, such as alkaline soils with high Ca and Mg contents. The use of chelating agents has shown promise in the composition of Zn fertilizer sources by reducing the dependence on the availability of this nutrient in these adverse soil conditions. In addition, the use of new molecules of these agents generates low envi- ronmental liabilities because they are rapidly biodegraded. Thus, the objective of this work was to study the effect of mineral sources and chelates of Zn on the availability and uptake of this nutrient by corn plants under the effect of soil textures and liming conditions. Two groups of studies were carried out, the first to investigate the effects of sources, pH and Ca and Mg activities on the kinetic parameters of Zn uptake by plants, and the second to analyze the effect of these same factors on plant development and Zn accumulation in plant tissues. For the estimation and validation of Zn uptake kinetic parameters in plants, an easy-to-use computer application was developed, accessible by the internet, where, besides the estimates of kinetic parameters K m , v max and c min , additional parameters and linear transformations of the Michaelis-Menten model, re- sults of statistical tests of significance and fits, and graphs of the fits are returned. To evaluate the effects of Zn sources, pH, and Ca and Mg concentrations and activities on Zn acquisition mechanisms by plants, an experiment was performed to obtain the pattern of Zn removal by plants from the culture solution. The data obtained in this experiment were used to obtain the depletion curve, relating the elemental amount of Zn in solution (q) as a function of time (t). From these curves were obtained the esti- mates of the maximum absorption velocity values for the saturated segment ( s v max ) of the depletion curve, and of K m , a v max , and c min and for the asymptotic segment (1st order). The fitting of the data to the models was performed using the Kinetica com- putational platform. The interpolate.LSQUnivariateSpline class of the SciPy (Python) computational library was employed for segmentation of the depletion curves, obtain- ing for each qxt curve two segments, the first characterized as order 0, describing an absorption pattern under saturated conditions of the absorption mechanisms, while the second segment was characterized as unsaturated, describing an asymptotic curve in relation to the abscissa axis of the q(t) function. The estimation of the parameter s v max (saturated segments) was obtained by the derivative of the order 0 model. For the asymptotic segment, the parameters K m , a v max and c min were estimated by the graph- mathematical method (RUIZ, 1985) and by direct fit to the Michaelis-Menten model. Finally, greenhouse experiments were conducted with corn plants grown under five doses of Zn (0, 4, 8, 16 and 32 mg kg -1 of the element) and three liming levels (pH 5.5, 6.5 and 7.5), related obtained by means of neutralization curves for each soil, and then dry matter production, and Zn content and content in plant tissues were evaluated. In general, Zn uptake was less intense and also less affected by soil conditions and lim- ing when the source employed was Zn–EDTA, while for ZnSO 4 this finding is inverted. Zn–EDDS showed an intermediate behavior, favoring Zn uptake in a balanced manner regardless of soil condition, and pH and Ca and Mg activities. Keywords: Chelates. Micronutrients. Overliming. Uptake kinetics. Web application.